Patterns-of-Care Analysis for Radiotherapy of Elderly Head-and-Neck Cancer Patients: A Trinational Survey in Germany, Austria and Switzerland - Haehl, Erik; Rühle, Alexander; Spohn, Simon; Sprave, Tanja; Gkika, Eleni; Zamboglou, Constantinos; Grosu, Anca-Ligia; Nicolay, Nils H. (Frontiers in Oncology, 2022)
Objectives The number of elderly head-and-neck squamous cell carcinoma (HNSCC) patients is increasing, and clinical trials defining the standard of care either excluded or underrepresented elderly patients. This lack of evidence leaves physicians with challenging and individual treatment decisions . Methods A trinational patterns-of-care survey was sent to all members of the German, Austrian, and Swiss national societies of radiation oncology. The online questionnaire consisted of 27 questions on the treatment of elderly HNSCC patients, including 6 case-based questions. Frequency distributions and subgroup comparisons were calculated using SPSS statistics software. Results A total of 132 radiation oncologists answered the questionnaire, including 46 (35%) from university hospitals, 52 (39%) from non-university-hospitals and 34 (26%) from private practices. Eighty-three physicians (63%) reported treatment of 1-5 and 42 (32%) of >5 elderly HNSCC patients per month. Target volumes are defined according to current guidelines by 50% of responders and modified based on age, comorbidities or tumor stage by 28% and 22% of radiation oncologists, respectively. Concomitant chemotherapy is routinely prescribed by 84% if indicated, with weekly 40mg/m2 cisplatin being the favored regimen by 53% of radiation oncologists in the definitive situation and 47% in the adjuvant setting. Hypofractionation and hyperfractionation/acceleration are routinely used by 20% and 9% of responders, respectively. Only 5% of radiation oncologists routinely recommend inpatient treatment for elderly HNSCC patients. In a representative case study of a 76-year-old patient with cT3 cN0 hypopharyngeal cancer, 63% of responders recommended definitive chemoradiation with bilateral elective node irradiation as per current guidelines. In a second case study regarding adjuvant treatment of a 74-year-old patient with HPV-positive pT2 pN1 oropharyngeal cancer, recommendations regarding elective volume and chemotherapy were heterogeneous. Differences between responders’ institutions concern the frequency of PET-CT for staging, preventive port-catheter and PEG implantation, the choice of chemotherapy regimens and the use of alternative fractionations. Conclusion Radiotherapy recommendations for elderly HNSCC patients were found to be heterogeneous among the different classes of treatment centers and were only partly based on guidelines established for younger patients. Therefore, improved algorithms for patient stratification and treatment recommendations especially for “unfit” elderly patients are needed.